A Query on the Components and Aspects of Critical Assessment of Academic Textbooks with an Emphasis on the Principles of Planning and Organizing Educational Messages - Mohammadreza Nili Ahmad Abadi; Ali Dana (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Textbooks have different features and dimensions that reviewing their quality requires studying, criticism, and evaluation from different perspectives. Therefore, this study aimed to provide some criteria for critical assessment of academic textbooks based on principles of educational messages. This is a qualitative library research in which the scientific resources such as books and articles have been studied inductively, and then, the topics were categorized and new criteria for critical assessment of textbooks were presented. The research population of this study included all information resources, books, and indexed articles in the accredited national and international journals published from 2001 to 2017. Moreover, the sampling method of this research was purposive non-random sampling. The results indicated that in the criticism of academic textbooks, other than regarding the formal, structural, content, and writing dimensions, there also exist two more dimensions of a high importance, i.e., the educational and research dimensions. Finally, it can be concluded that in the criticism of academic textbooks, the first purpose of which is the transmission of an educational message, if the educational and research dimensions are ignored, the critique of the book would stay inapplicable and would not satisfy its goals.